Prevalence of metabolic syndrome and its associated risk factors in an African–Caribbean population with severe mental illness. (November 2019) - de Caluwé, Laura; van Buitenen, Nora; Gelan, Petra J.; Crunelle, Cleo L.; Thomas, Roeland; Casseres, Sharon; Matthys, Frieda; van Harten, Peter; Cahn, Wiepke
Highlights: Alarmingly high prevalence of metabolic syndrome noted in African–Caribbean patients. Female patients were 4 times more likely to be diagnosed with the metabolic syndrome. Outpatient setting was associated with greater odds of having metabolic syndrome. Substance use disorder was associated with lower odds of having metabolic syndrome. Metabolic abnormalities were more prevalent in patients than in the general population. Abstract: This cross-sectional study aims to determine the prevalence of metabolic syndrome (MetS) in patients with severe mental illness (SMI) on a Caribbean island, Curaçao, using the modified National Cholesterol Education Program Adult Treatment Panel III criteria. Among 350 patients (240 men and 110 women) with a mean age of 51.9 years ( S.D. =13.5) MetS prevalence was 37.4%, significantly higher in female patients (63.6%) compared to male patients (25.4%). Increased waist circumference was present in 51.1%, low HDL in 50.6%, hypertension in 49.4%, hyperglycemia in 28.6% and 25.7% had hypertriglyceridemia. Except for hypertriglyceridemia, all criteria were more prevalent in female patients. Binary logistic regression analysis indicated that female gender, outpatient treatment setting and the absence of substance use disorder were all significant predictors for MetS. Compared to data from the general population obtained by the 2013 National Health Survey Curaçao, this study showed significantly higher prevalence of diabetes and hypertension in patients with SMI. Moreover, female patients had the highest prevalence of diabetes (28.2%), obesity (50.0%) and increased waist circumference (88.2%). This study demonstrates that African-Caribbean patients with SMI are at high-risk for MetS, especially female patients. Our data suggest to focus on modifiable lifestyle risk factors, as promoting physical activity and healthy dietary habits.